Therapeutic Drug Monitoring of Olanzapine and Cytochrome P450 Genotyping in Nonsmoking Subjects. Issue 2 (April 2020) - Miroshnichenko, Igor I.; Pozhidaev, Ivan V.; Ivanova, Svetlana A.; Baymeeva, Natalia V.
Abstract : Background: The relationship between a daily dose of olanzapine, its serum concentration, and the genotype of young nonsmoking men treated for schizophrenia or schizophreniform disorder was investigated in day-to-day clinical practice. Pharmacogenetics was also examined for the selected patients. Methods: A total of 49 participants were recruited as in-patients at the Mental Health Research Center (Moscow, Russia). Inclusion criteria were patients who had been diagnosed with schizophrenia or schizoaffective disorder (following DSM-IV guidelines) and were being treated with OLZ. A prospective, observational, open-study design was implemented. In line with the literature, patients were only included if they attained steady-state OLZ concentrations lasting for at least 8 days. A liquid chromatographic–tandem mass spectrometric method was developed for analyzing OLZ in human serum. The single cytochrome P450 polymorphisms were genotyped using an amplifier real-time polymerase chain reaction system following standard protocols. Results: Evidence indicating that CYP2D6 polymorphism has a significant ( P = 0.046) effect on the pharmacokinetics of olanzapine was obtained, confirming the beneficial effects of therapeutic drug monitoring (TDM) for olanzapine. Conclusions: TDM should therefore be used as a standard care during olanzapine therapy. TDM is also useful in assessing adherence and may have a role in limiting olanzapine dosage geared at minimizing the risk of long-term toxicity.